2015
DOI: 10.1165/rcmb.2014-0227oc
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DRB1 with Sarcoidosis Susceptibility and Progression in African Americans

Abstract: HLA-DRB1 is a sarcoidosis risk gene, and the *03:01 allele is strongly associated with disease resolution in European sarcoidosis cases. Whereas the HLA-DRB1 variation is associated with sarcoidosis susceptibility in African Americans, DRB1 risk alleles are not as well defined, and associations with disease resolution have not been studied. Associations between genotyped and imputed HLA-DRB1 alleles and disease susceptibility/resolution were evaluated in a sample of 1,277 African-American patients with sarcoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 50 publications
7
24
0
Order By: Relevance
“…Sarcoidosis often shows an unpredictable disease course. Clinical manifestations also vary with the organs involved [5][6][7]. In our study, deteriorating FVC and DLCO values were also more frequent in HLA-DRB1*014 and HLA-DRB1*15 positive patients.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sarcoidosis often shows an unpredictable disease course. Clinical manifestations also vary with the organs involved [5][6][7]. In our study, deteriorating FVC and DLCO values were also more frequent in HLA-DRB1*014 and HLA-DRB1*15 positive patients.…”
Section: Discussionsupporting
confidence: 56%
“…The cause of sarcoidosis and its wide phenotopic differences are not yet fully understood [4]. Prevalence in different ethnic groups, familial occurrence, and its high incidence among monozygotic twins suggests genetic predisposition and several studies indicate that HLA antigens are more frequent in patients with sarcoidosis and genetic factors may play an important role in modifying the risk for the disease, its phenotype, and outcome [1,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Levin et al [58] genotyped a large population of African American patients (n ¼ 1277) and matched controls (n ¼ 1467), and found that, consistent with previous findings among individuals of European descent [57], carriage of the HLA-DRB1…”
Section: Sarcoidosissupporting
confidence: 75%
“…Levin et al further showed carriage of DRB1*0301 decreased risk for extra-pulmonary manifestations of sarcoidosis in non-thoracic lymph nodes, eyes, skin and liver 12 . Alternatively, carriage of DRB1*0302 increased risk for skin involvement in African American sarcoidosis patients.…”
Section: Introductionmentioning
confidence: 96%
“…Levin et al examine DRB1 variation in the context of disease phenotype in 1,277 African Americans patients and 1,468 controls 12 . They found that the DRB1*03:02 allele conferred a similar likelihood of resolving disease in African American sarcoidosis patients as *03:01 -positivity does in Europeans 14 .…”
Section: Introductionmentioning
confidence: 99%